ChemInform Abstract: Polyoxometalate‐ionic Liquids (POM‐ILs)‐the Ultimate Soft Polyoxometalates? A Critical Perspective. Issue 7 (29th January 2015) - Herrmann, Sven; Seliverstov, Andrey; Streb, Carsten
Abstract Review: 60 refs.